Madness in medieval French literature identities found and lost - Huot, Sylvia (Oxford University Press, 2003)
Madness is a frequent theme in medieval French literature. This title presents a variety of texts which illustrate the wide range of attitudes towards madness and its uses as a literary device, tying in with contemporary interest in the politics of identity, and its literary constructions.